PENGARUH KUALITAS PELAYANAN WAITER/ WAITRES TERHADAP KEPUASAN TAMU D’CAFE RESTAURANT DI HOTEL AXANA PADANG - Ramadani, Betria; Kasmita, Kasmita; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This study aimed to 1) analyze the quality of service waiter/waitress in D‟Cafe Restaurant Hotel Axana Padang, 2) analyze guest satisfaction with service waiter/waitress in D‟Cafe Restaurant Hotel Axana Padang, 3) analyze the influence of the quality of service waiter/waitress to guest satisfaction D‟Cafe Restaurant Hotel Axana Padang. This study uses causal associative, variable inthis study is the quality of service waiter/waitress (X) and guest satisfaction (Y). The sampling technique used is incidental sampling. The number of 91 people, collecting data used were questionnaires. Quality of service waiter/waitress percentage of 42% is in the range score of 36-<44 with enough category and guest satisfaction percentage of 41% is in the range score of 36-<44 with enough category. Test hypothesis Simple linear regression FCount with sig 0,000 <0,05 then there is significant influence between quality of service waiter/waitress (X) to guest satisfaction (Y) as big 74% and 26% of other factors. Keyword : Quality of service waiter/waitress and guest satisfaction1 Prodi